Social network analysis : a case study of an educational institute. - Chang, Yi Ching. (2008)
A social network analysis study is conducted on an educational institute in Singapore. Through various methods and with the usage of a social network analysis application NetMiner, visual maps of various networks are generated. With these, it becomes possible to identify the highly-connected and disconnected employees, and propose alternatives to improve the situation.